2008
DOI: 10.1111/j.1651-2227.1994.tb13098.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of inflammatory bowel disease in children in South-Western Sweden

Abstract: Hildebrand H, Brydolf M, Holmquist L, Krantz I, Kristiansson B. Incidence and prevalence of inflammatory bowel disease in children in South‐Western Sweden Acta PEdiatr 1994;83:640–5. Stockholm. ISSN 0803–5253 The incidence and prevalence of inflammatory bowel disease were estimated in all children less than 16 years of age living in the city of Göteborg and in three counties in South‐Western Sweden, from 1983 to 1987. One hundred and thirty‐two patients were classified according to set criteria into one of fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 21 publications
4
25
0
Order By: Relevance
“…Our findings have shown that IBD-indeterminate has a distinctive clinical pattern of IBD in children with a higher prevalence than that reported in adults 9,10. Only a small number of the studied IBD-indeterminate children were reclassified to either CD or UC, similar to what has been reported by Lindberg and coworkers11 in a Swedish based population study of children with indeterminate colitis (IC).…”
Section: Discussionsupporting
confidence: 88%
“…Our findings have shown that IBD-indeterminate has a distinctive clinical pattern of IBD in children with a higher prevalence than that reported in adults 9,10. Only a small number of the studied IBD-indeterminate children were reclassified to either CD or UC, similar to what has been reported by Lindberg and coworkers11 in a Swedish based population study of children with indeterminate colitis (IC).…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we have shown IC to be a clinically distinct subgroup of pediatric patients with IBD with a higher prevalence than that reported in adults 13,14. Although 34% of the original IC group was reclassified to either CD or UC, most were reclassified after <2 years of follow‐up.…”
Section: Discussionmentioning
confidence: 57%
“…A total of 2209 references were reviewed, resulting in 139 included studies7–145 from 32 countries (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%